Indications that long-term nitrogen loading limits carbon resources for soil microbes. (December 2017) - Rappe-George, M.O.; Choma, M.; Čapek, P.; Börjesson, G.; Kaštovská, E.; Šantrůčková, H.; Gärdenäs, A.I.
Abstract: Microbial communities in the organic horizon (O-horizon) of forest soils play key roles in terrestrial nitrogen (N) cycling, but effects on them of long-term high N loading, by N deposition or experimental addition, are not fully understood. Thus, we investigated N-loading effects on soil microbial biomass N, carbon (C) and phosphorus stoichiometry, hydrolytic and oxidative enzymes, community composition (via phospholipid fatty acids, PLFA) and soil chemistry of the O-horizon in study plots of three well-studied experimental Norway spruce ( Picea abies ) forests in Sweden and the Czech Republic. These forests span substantial gradients in current N deposition, experimental N addition and nitrate (NO3 − ) leaching. Current N deposition ranges from ∼3 kg ha −1 year −1 of N in central Sweden (Stråsan) to ∼15 kg ha −1 year −1 of N in SW Sweden (Skogaby) and Czech Republic (Čertovo). Furthermore, accumulated historical N loading during 1950–2000 (which include experimental N addition performed at Stråsan and Skogaby) ranged ∼200–∼2000 kg ha −1 of N. Across all sites and treatments, current NO3 − leaching ranged from low (∼0.1 kg ha −1 year −1 of N) at Stråsan, to high (∼15 kg ha −1 year −1 of N) at Skogaby and Čertovo. We found significantly lower C/N ratios and greater amounts of extractable inorganic N species in the forest soils' O-horizons at the high N loading plots. Microbial biomass and basal respiration decreased under experimental N addition treatments and tended to decrease with increased N deposition. Similarly, activities of hydrolytic enzyme activity associated with N acquisition were lower, although differences in activities at specific sites with the highest and intermediate historical N deposition levels failed statistical significance. Conversely, activities of soil hydrolytic enzymes associated with C acquisition were greater in study plots exposed high N loading. PLFA profiles indicated shifts in microbial community composition induced by long-term N load, towards higher and lower relative abundance of Gram-positive and Gram-negative bacteria, respectively (but no changes in fungal relative abundance). Taken together, our results suggest that long-term N loading of N-limited Norway spruce forests aggravates limitation of other resources, likely of C, for soil microbial communities. Although microbial variables in the soil O-horizon differed between plots exposed to low and high current N loading, microbial variables in plots that leached small amounts and large amounts of NO3 − exposed to high N load were similar. Highlights: Long-term nitrogen load decreased forest soil microbial biomass and respiration. Soil enzyme activities were affected by long-term nitrogen loading. Long-term nitrogen load induced shifts in soil phospholipid fatty acids. Soil microbial variables were similar despite varying ecosystem nitrogen retention.